Slope Stability Analysis Some Selected Sites at Bajalia Anticline in Missan Governorate, Eastern Iraq - Al-Zubaydi, Jaffar H.Ali; Al-Turaihi, Ahmed S. (Iraqi Journal of Science, 2024)
In this study, rock stability has been assessed to pinpoint the critical factors affecting slope instability. The discontinuity data collected during the field surveys was evaluated using stereograph projection. Bai Hassan, Mukdadiya, and Injana Formations that were exposed in the research region show slope collapses, ranging in severity from most to least in terms of secondary toppling and rock fall. The characteristics of the rock discontinuities determine the kind and extent of hazards. According to this study, warning signs and fencing should be used to prevent people from walking along the edges of the slopes in the Bajalia anticline and the areas around to alert them of potential failure threats.